2020
DOI: 10.1002/mgg3.1506
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CNVs of CFTR gene in Chinese Han population with CBAVD

Abstract: Congenital bilateral absence of vas deferens (CBAVD) is an important disease of male infertility, accounting for 1%-2% of infertile population (Jequier, Ansell, & Bullimore, 1985; Yu, Chen, Ni, & Li, 2012). CBAVD is characterized by absence of vas deferens and semen abnormality (Practice Committee of the American Society for Reproductive Medicine in collaboration with the Society for Male & Urology, 2018). Cystic fibrosis (CF) is a well-known genetic disease, and showed racial differences (it is common in Cauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The majority of patients with CAVD carried at least one mutation, but only 11.11% of them carried more than one mutations. This result is similar to other studies in Chinese men (Jiang et al, 2014;Ma et al, 2020;Yang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The majority of patients with CAVD carried at least one mutation, but only 11.11% of them carried more than one mutations. This result is similar to other studies in Chinese men (Jiang et al, 2014;Ma et al, 2020;Yang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Our top 3 common mutations (exon 16-17b deletion; c.1322T>C, p.Leu441Pro; c.3871C>T, p.Gln1291Ter) were mostly restricted to Asian patients. 17 30 31 We observed sufficient L441P-CFTR L441P-CFTR correction by VX809 and VX661. 17 Our findings indicate that CFTR modulators can functionally improve CFTR channels in patients with the p.Leu441Pro mutation.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, the role of this mutation in azoospermia requires confirmation in a larger patient cohort. Recent research reported that among 263 Chinese patients with CBAVD, 5 (1.9%) patients were detected for copy number variants in the region of the CFTR gene (four of them carried partial deletions and one carried partial duplication of CFTR ), 37 but other studies did not find copy number variations of CFTR in males with CBAVD. 38 , 39 A larger number of samples and more sensitive gene detection methods are essential for further research.…”
Section: Discussionmentioning
confidence: 95%